Chemical constituents of Asparagus - Negi, J. S.; Singh, P.; Joshi, G. P.; Rawat, M. S.; Bisht, V. K. (Pharmacognosy Reviews)
Asparagus species (family Liliaceae) are medicinal plants of temperate Himalayas. They possess a variety of biological properties, such as being antioxidants, immunostimulants, anti-inflammatory, antihepatotoxic, antibacterial, antioxytocic, and reproductive agents. The article briefly reviews the isolated chemical constituents and the biological activities of the plant species. The structural formula of isolated compounds and their distribution in the species studied are also given.
Keywords: Asparagus species; isolated compounds; sarsasapogenin; steroidal saponins